Development of high current source / Mohd. Saleh Shamlani - Shamlani, Mohd. Saleh (1995)
The development of high current source with the combination of theoritical and practical aspect of simple transformer. The main idea behind the development of this project is initially to cater for the requirement of the water absorption and Ac load cyclic test of high voltage cable jointing and termination. Results of the proposed prototype and the problem arise in the laboratory are explained briefly for future improvement With basic design and availability of the basic components, an initial desired value had been achieved.